Study on the Compaction Effect Factors of Lime-treated Loess Highway Embankments - Yuyu Zhang; Wanjun Ye; Zuoren Wang (Salehan Institute of Higher Education, 2017)
This paper presents a study to investigate the effects of water content, lime content and compaction energy on the compaction characteristics of lime-treated loess highway embankments. Laboratory compaction tests were conducted to determine the maximum dry density and optimum water content of loess with different lime Contents (0, 3, 5 and 8%), and to examine the effects of water content, lime content and compaction energy on the value of and . In situ compaction tests were performed to obtain the in situ dry density and the degree of compaction of different lime-treated loess. Experimental embankments with different fill materials (0, 3, 5 and 8% lime treated loess) were compacted by different rollers during in situ tests. The results indicate that increases due to the increase of water content . Once water content exceeds , dry density decreases dramatically. The addition of lime induced the increase of and the decrease of . A higher compaction energy results in a higher value of and a lower value of . The value of achieves it’s maximum value when in situ water content was larger than the value of (+1-2%). The degree of compaction can hardly be achieved to 100% in the field construction of embankments. Higher water content and compaction energy is needed for optimum compaction.